Perbedaan kadar hemoglobin pada mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi berdasarkan kualitas tidur - Sarjono, Lillian; Pandelaki, Karel; Ongkowijaya, Jeffry (e-CliniC, 2016)
Abstract: Sleep is defined as a subconscious condition when the individual may be arose from sleep by giving him or her with stimulation which is a crucial process for human beings in the formation of new body cells, the improvement of damaged cells, and to maintain the balance of body metabolism and biochemistry. The quality of sleep described by less time of sleep have impact on the body, as biological process taking place at the moment of sleep would be disturbed. One of them is disturbance in the formation of hemoglobin in which a change shall be occurring where the content of hemoglobin is lower than its normal value. This study is analytical descriptive using a cross-sectional approach. Of 78 samples under study, the good quality sleep is 7 persons (9.0%) and the bad is 71 persons (91.0%). Normal content of hemoglobin is 40 person (51.3%) and abnormal is 38 persons (48,7%). The good quality sleep and normal content of hemoglobin is 4 persons (57.1%) and abnormal is 3 persons (42.9%). The bad quality sleep and normal content of hemoglobin is 36 persons (50.77%) and abnormal is 35 persons (49.3%). Conclusion: Most of students at Faculty of Medicine, Sam Ratulangi University, have bad quality sleep and normal content of hemoglobin. There are no differences between the content of hemoglobin from the 5th semester student in Medical Faculty student with who has good and bad sleep quality.Keywords: quality of sleep, hemoglobinÂ Abstrak: Tidur didefinisikan sebagai suatu keadaan bawah sadar saat orang tersebut dapat dibangunkan dengan pemberian ransangan yang juga merupakan proses yang sangat dibutuhkan manusia untuk pembentukan sel-sel tubuh yang baru, perbaikan sel-sel tubuh yang rusak maupun untuk menjaga keseimbangan metabolisme dan biokimiawi tubuh. Kualitas tidur yang digambarkan dengan waktu tidur yang kurang akan membawa dampak bagi tubuh karena proses biologis yang terjadi saat tidur akan ikut terganggu. Salah satunya adalah pembentukan kadar hemoglobin yang terganggu dimana akan terjadi perubahan dimana kadar hemoglobin menjadi lebih rendah dari nilai normalnya. Penelitian ini bersifat deskriptif-analitik dengan pendekatan potong lintang. Dari 78 sampel pemelitian, kualitas tidur yang baik sebanyak 7 orang (9,0 %) dan yang buruk sebanyak 71 orang (91,0 %). Kadar hemoglobin normal sebanyak 40 orang (51,3 %) dan tidak normal sebanyak 38 orang (48,7 %). Kualitas tidur baik dengan kadar hemoglobin normal adalah 4 orang (57,1 %) dan kadar hemoglobin tidak normal adalah 3 orang (42,9 %). Kualitas tidur buruk dengan kadar hemoglobin normal adalah 36 orang (50,7 %) dan kadar hemoglobin tidak normal adalah 35 orang (49,3 %). Simpulan: Sebaigan besar mahasiswa Fakultas Kedokteran Unsrat mempunyai kualitas tidur yang buruk dan mempunyai kadar hemoglobin yang normal. Tidak terdapat perbedaan kadar hemoglobin pada mahasiswa semester 5 Fakultas Kedokteran Unsrat dengan kualitas tidur yang baik dan yang buruk. Kata kunci: kualitas tidur, hemoglobin